SHIFTS OF INTERPERSONAL MEANINGS IN TRANSLATED NEWS REPORTS OF AN INDONESIAN LOCAL NEWSPAPER - Afrida Sasyalia Sakinah, - (2018)
This research aims to analyze the interpersonal meanings shifts of the translated articles in Pikiran Rakyat as a local newspaper, and investigates how the shifts realize potential ideological meanings. This study applies a qualitative method of data collection and analysis. The data of this study were taken from articles written in Pikiran Rakyat and its original sources were taken from BBC and The Guardian news portals. The data were analyzed by using Appraisal Theory which was developed by Martin and White (2005). The analysis shows that the shifts comprised clause shifts, subject shifts, and appraisal shifts. Clause shift was employed in the titles of the translated articles and it affects the focus of the report in the articles. Subject shift was employed to diminish subjectivity, to add distance to the topic that is being talked about, and to make the readers discover what is delivered in the articles. In terms of appraisal shifts, the most dominant sub-strategy employed was the employment of intensifying appraisal items on the target texts to deliver the news as equivalent to the original texts. The potential ideological meanings found in the translated articles were affected by the local newspaper's value. These findings confirm Al-Mohannadi's (2008) and Pan's (2014) studies that interpersonal meanings in translated news reports are determined by the translators and that media play role to mediate news. -----